Investigating the incorporation of education about, in/through and for the environment in the Geography junior phase curriculum: a case study of three Namibian schools - Anyolo, Eveline Omagano (Rhodes University, Faculty of Education, Department of Education, 2012)
This study was carried out to investigate how education about, in/through and for the environment is incorporated in the Namibian Geography Junior Phase curriculum in three schools in Oshana Education Region. Education about, in/through and for the environment are three forms of environmental education identified by Fien (1998). This study is a qualitative, interpretive case study. It reviews the activities, content knowledge, methods, competencies and resources and describes how they were used by teachers in fostering education about, in/through and for the environment in the curriculum. Data was generated through document analysis, observations and semi-structured interviews. The results were interpreted and discussed in relation to the research question which is: How is education about, in/through and for the environment incorporated in the Geography Junior Phase curriculum? Key findings of the study suggested that teachers incorporated education about, in/through and for the environment in their teaching. Teachers used the prescribed syllabus to structure their environmental learning lessons. Most methods, resources and activities used by the teachers promoted education about the environment. The study also found that most types of knowledge about the environment were covered by the teachers. This enabled learners to examine the complexity and interrelatedness of natural systems. The study found that the way the resources were used exclusively supported education about the environment. Linking learning to local context in this study encouraged education in/through the environment and enhanced the learning process through real life experience. The study also found that, although teachers taught their learners for the environment, they did not empower them in taking actions towards environmental problems. Based on the insights offered by this research, the study identified further support required by teachers and made recommendations for effective incorporation of about, in/through andfor the environment in the curriculum.
Keywords: Environmental education -- Namibia -- Case studies; Education, Primary -- Curricula -- Namibia; Geography teachers -- Namibia -- Case studies